Psychological intervention program in victim students of bullying - Cabanillas Zuloeta, Jennifer Sadith (2019)
The objective of this research was to determine the influence of a psychological intervention program for bullying rates in secondary school students, the type of research was applied with a quantitative approach, its pre-experimental design, as a population and sample is considered to be 20 First grade students, the technique used was the survey and as a tool a questionnaire of 25 articles was used whose application is to specifically know the level of the study variable, which could be applied collectively with the duration of 15 minutes. Likewise, it should be noted that in order to facilitate the understanding of the results of the analysis carried out the items that had the response: never, almost never, sometimes, almost always and always. As a main result, after applying the normality test and the Wilcoxon test it was found that the Sig (0.015) < p-value (0.05) thus rejecting H0. Therefore, as the conclusion was limited if a Psychological Intervention program is applied, it is possible to reduce the levels of bullying in high school students.